The Unholy Trinity of Software Development. - Neville-Neil, George V. (Communications of the ACM, 2017)
The article presents questions and answers related to software development, including how to get software teams to adopt more holistic approaches to system integration and the testing and documenting of computer systems, and reasons for an increase in the number of CPU cores available to software despite no changes in frequency.